1980
DOI: 10.1148/radiology.137.1.7422831
|View full text |Cite
|
Sign up to set email alerts
|

Infarctions of the brainstem and cerebellum: a correlation of computed tomography and angiography.

Abstract: Forty-nine patients were found to have computed tomographic (CT) and clinical evidence for infarction in the brainstem and cerebellum. Seventeen had correlative angiography, of which 15 had a severe occlusive vascular lesion somewhere in the vertebrobasilar system. The correlation between angiographic and CT localization of the infarcts was not good. Inferiorly located infarcts were probably often missed on CT because of basal artifacts. Combined infarctions of the brainstem and cerebellum were common. Ninetee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0
2

Year Published

1984
1984
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(13 citation statements)
references
References 0 publications
1
10
0
2
Order By: Relevance
“…A male preponderance has been suggested for CI [1]in elderly, but the sexes were equally distributed in our study. In accordance with others [3, 17, 18, 21, 22], the PICA and SCA territory were almost equally often involved and AICA territory infarcts infrequently. Nonterritorial or junctional infarcts have frequently been reported in elderly populations [20, 22], but occurred sporadically in this study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A male preponderance has been suggested for CI [1]in elderly, but the sexes were equally distributed in our study. In accordance with others [3, 17, 18, 21, 22], the PICA and SCA territory were almost equally often involved and AICA territory infarcts infrequently. Nonterritorial or junctional infarcts have frequently been reported in elderly populations [20, 22], but occurred sporadically in this study.…”
Section: Discussionsupporting
confidence: 90%
“…However, in patients above 45 years studied by the same research group the differences were less pronounced and among infratentorial structures, the cerebellum (47%) was almost as often affected as the brainstem (59%) [15]. In other studies consisting mainly of elderly patients, the proportion of CI among patients with ischemic stroke ranges from 0.6 to 2.8% [16, 17, 18, 19], but a center with special interest in CI recently reported a proportion of 10.4% CI [20]. …”
Section: Discussionmentioning
confidence: 99%
“…The frequency of cerebellar infarcts has been estimated to be 0.7% in neuroradiological studies [25,26] and 1.5-4.2% in autopsy series [27,28]. Most of these patients have a pure cerebellar syndrome with a benign course of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…31,32], Greenberg et al [6] reported successful treatm ent of cerebellar in farction with sole ventriculostomy in 2 patients. In a large retrospective CT study, H inshaw et al [25] recommended medical therapy to be sufficient for the majority of patients presenting with posterior fossa infarcts. How ever, most of their cases did not show severe spaceoccupying posterior fossa mass lesions.…”
Section: Discussionmentioning
confidence: 99%
“…EVD has been favored in many reports 5,10-14 and craniectomy has been performed in some reports. [15][16][17][18][19][20][21][22] Recently, it has been reported that EVD is done as the first step, and then craniectomy with or without resection is added in the case of there being no recovery of the neurologic condition after EVD. 1,[3][4][5][6][7] This opinion seems to be reasonable.…”
Section: Discussionmentioning
confidence: 99%